Characterization of DNA Quality, TPOX Locus, TH01 Locus in Seawater Soaked Nails in Forensic Identification - Utomo, Ratno Tri; Endarini, Lully Hanni; Yudianto, Ahmad; Christyaningsih, Juliana (Poltekkes Kemenkes Palu, 2023)
Forensic science is multiplying. One of them is the identification of events at sea. Of course, the victim’s body can be submerged in seawater for days so that components in seawater can affect the victim’s body. This research aimed to see the effect of storage time on the level and purity of DNA in nail samples. Identification of nail DNA using the Polymerase Chain Reaction (PCR) method. The DNA purity test examines nail samples using a spectrophotometer read at 260 and 280 nm wavelengths. Measurement of DNA levels using the PCR instrument on the STR TPOX locus, the result was 32.02 ug/uL on positive control, 36.73 ug/uL in seawater immersion on the 2nd day, 35.35 ug/uL in seawater immersion on the 7th day, and 34.5 ug/uL in seawater immersion on the 20th day. At the STR TH01 locus, the result was 32.155 ug/uL on positive control, 38.05 ug/uL on the 2nd day of immersion in seawater, 35.18 ug/uL on the 7th day, and 33.88 ug/uL on the 20th day. Results Examination of the Total Plate Number of seawater on the 2nd day, 7th day, and 20th day of immersion found no colonies of germ colony growth. This study obtained sufficient DNA purity from the 2nd day, 7th day and 20th day. So that the samples could be analyzed for DNA levels, the result obtained from the study showed a decrease in DNA levels at the TPOX Locus and TH01 Locus from the 2nd day, 7th day, and 20th day.